2012
DOI: 10.1002/jbmr.1676
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-dose calcium supplements on bone loss in perimenopausal and postmenopausal Asian women: A randomized controlled trial

Abstract: Current standard-dose calcium supplements (eg, 1000 mg/d) may increase the risk for cardiovascular events. Effectiveness of lower-dose supplements in preventing bone loss should thus be considered. This study aimed to assess whether calcium supplements of 500 or 250 mg/d effectively prevent bone loss in perimenopausal and postmenopausal Japanese women. We recruited 450 Japanese women between 50 and 75 years of age. They were randomly assigned to receive 500 mg of calcium (as calcium carbonate), 250 mg of calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 25 publications
(26 reference statements)
1
21
0
Order By: Relevance
“…Both calcium supplement users and non-users lost BMD at all three sites, suggesting that calcium supplementation at this dose may not have a protective effect on BMD. This is consistent with a 2012 study that found a calcium supplement dose below 500 mg/day did not offer any BMD protection to femoral neck or total hip sites in older women [40]. It has been proposed that low-dose calcium supplements are most effective at preventing BMD loss in women with low dietary calcium intake (< 400 mg/day) [41].…”
Section: Discussionsupporting
confidence: 87%
“…Both calcium supplement users and non-users lost BMD at all three sites, suggesting that calcium supplementation at this dose may not have a protective effect on BMD. This is consistent with a 2012 study that found a calcium supplement dose below 500 mg/day did not offer any BMD protection to femoral neck or total hip sites in older women [40]. It has been proposed that low-dose calcium supplements are most effective at preventing BMD loss in women with low dietary calcium intake (< 400 mg/day) [41].…”
Section: Discussionsupporting
confidence: 87%
“…Supplementation of as low as 500 mg of calcium could effectively slow lumbar spine bone loss in Japanese perimenopausal women with low calcium intake [Nakamura et al, ]. Similar beneficial effects have been observed in postmenopausal women from Hong Kong [Lau et al, ; Haines et al, ; Lee et al, ; Lau et al, ; Ho et al, ], China [Gui et al, ], Chile [Rodriguez and Novik, ], Argentina [Malpeli et al, ] and Nigeria [Umaretiya et al, ].…”
Section: Implications In Global Health Perspectives – Fracture and Camentioning
confidence: 86%
“…In the second study, 450 perimenopausal women (up to the age of 75 years) were randomly assigned to receive 500 mg or 250 mg of calcium (as calcium carbonate), or placebo daily (mean baseline calcium intake of 493 mg/day) (Nakamura et al . ). The higher dose was effective at reducing bone loss in the pre‐menopausal women who had low baseline intake of calcium.…”
Section: Personalising Nutrition For Older Adultsmentioning
confidence: 97%